ANALISIS PEMASARAN MEMASUKI PASAR PERSAINGAN ARABIKA KOPI DESA TALIMBARU BARUS JAHE - Siburian, Fandri; Marpaung, Posman HP (JURNAL AGROTEKNOSAINS, 2023)
Coffee plants are one of the plantations that play an important role in the Indonesian economy. Important roles include a source of income for small scale coffee farmers, while large ones, earning foreign exchange, providing employment opportunities and other economic actors involved in cultivation, processing and the marketing chain.Indonesia is called the largest coffee producing country in the world, the main target of coffee export activities is to market coffee products produced directly by Indonesian farmers.European countries, America and Japan are the largest consumer countries for coffee exports. Progress and developments over time have ultimately led to increased welfare and changes in the lifestyle of the Indonesian people, leading to increased coffee consumption. It was concluded from the marketing analysis and consumption levels that the balance in meeting coffee needs for (export) foreign and domestic markets (national level) must be increased by national coffee production. Coffee production in Indonesia is estimated at around 1.2 million hectares, spread across Java, North Sumatra and Sulawesi.Indonesia is one of the countries where the productivity of Arabica coffee is higher than the productivity of Robusta coffee, which is starting to be popular with farmers and coffee connoisseurs in Indonesia. Arabica coffee is one of the world's high demand coffees, which has contributed to Indonesia becoming the largest coffee producer to increase the production and productivity of Arabica coffee, which has a fairly high price.In improving knowledge, skills and attitudes with the aim of increasing coffee productivity, farmer groups have begun to be embraced and formed through deliberations or seminars as a means of learning for their members so that the problems faced by coffee farmers in Talimbaru Village regarding coffee productivity can no longer make mistakes in farming and lack of knowledge in the workforce and the operation of coffee processing equipment to achieve higher production.With this background, the author conducted research on marketing analysis entering the Arabica Coffee Competition Market in Talimbaru BarusJahe Village.